2023
DOI: 10.1021/acs.energyfuels.2c03764
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of Wax Crystal-Water Droplet Aggregations on Wax Deposition of Water-in-Oil Emulsions

Abstract: Wax deposition in waxy crude oil emulsions remains a flow assurance challenge in offshore production. Wax molecular diffusion driven by the positive temperature gradient from the liquid to the pipe wall has been widely studied and regarded as the primary wax deposition mechanism; however, a considerable wax deposit of emulsions at a zero-temperature difference was detected, in which condition molecular diffusion is not likely to occur, suggesting there were other mechanisms that contribute to wax deposition. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It was observed that increasing the temperature difference between the oil and the wall led to the formation of smaller and denser wax crystal particles at the deposit–oil interface, while increasing the shearing in the pipe flow reduced the number of wax crystal particles precipitated at the deposit–oil interface. Moreover, as shown in Figure , Ma et al. , pointed out that At zero temperature difference, water droplets alter the original structure of waxy oil, leading to wax crystals being linked to the water droplets through interfacial adsorption, or the water droplets being enveloped within a crystal network to form wax crystal-water droplet aggregates. Migration and adhesion of aggregates to the cold wall form the wax deposits of the emulsion.…”
Section: Wax Deposition Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…It was observed that increasing the temperature difference between the oil and the wall led to the formation of smaller and denser wax crystal particles at the deposit–oil interface, while increasing the shearing in the pipe flow reduced the number of wax crystal particles precipitated at the deposit–oil interface. Moreover, as shown in Figure , Ma et al. , pointed out that At zero temperature difference, water droplets alter the original structure of waxy oil, leading to wax crystals being linked to the water droplets through interfacial adsorption, or the water droplets being enveloped within a crystal network to form wax crystal-water droplet aggregates. Migration and adhesion of aggregates to the cold wall form the wax deposits of the emulsion.…”
Section: Wax Deposition Mechanismmentioning
confidence: 99%
“…Gelation deposition mechanism of water-in-oil emulsion presented by Ma et al , (a) Water droplets engineered to act as carriers for wax crystals to mitigate wax deposition in emulsions . (b) The gel temperature and viscosity altered as wax crystal-water droplet aggregates formed . (c) Mechanism of wax deposition in emulsions .…”
Section: Wax Deposition Mechanismmentioning
confidence: 99%
See 3 more Smart Citations